Management of Outdoor Education in Developing Naturalistic Intelligence and Early Childhood Character - Dini Lidinillah; Sri Handayani (Dinasti International Journal of Education Management and Social Science, 2025)
This research analyzes the management of Outdoor Education in developing naturalistic intelligence and early childhood character at TK Plus Al-Muttaqin, aiming to identify implementation conditions, needs, managerial obstacles, and formulate an effective and contextual management model. Employing a qualitative approach with a single case study design, this study involves participatory observation, in-depth interviews, and documentation analysis. The findings indicate that Outdoor Education management at TK Plus Al-Muttaqin has been implemented systematically and integrally through comprehensive planning, organizing, actuating, and controlling functions, aimed at fostering naturalistic intelligence and children's character via direct nature-based learning experiences. However, implementation faces internal barriers such as variations in children's characters and teacher consistency challenges, alongside external constraints including limited facilities, land, and inconsistent support from overprotective parents. In response, this study successfully develops an Outdoor Education management model integrating POAC principles, multiple intelligences theory, character education, and Early Childhood Character Curriculum principles, supplemented by innovative strategies to address barriers. The proposed model offers a comprehensive, applicable, and contextual framework, contributing to early childhood education management practices that optimize naturalistic intelligence and character development from an early age.